(untitled) (Gestionar: revista de empresa y gobierno, 2024)
This article explores the Colombian regulatory developments for the implementation of the Standard Specifications. It focuses on regulatory developments in the field of state procurement of transportation infrastructure and its potential benefits in the fight against corruption. These range from Law 80 of 1993 to Law 2022 of 2020 and its subsequent developments throughout 2020 and 2021. They are currently in the process of implementation. Thus, the aim is to observe whether the regulatory development of the Standard Specifications maintains the initial spirit of the norm that sought to put an end to the perverse effects of the Tailor Documents in the contracting processes of transport infrastructure works. The methodological development is based on the qualitative approach, with a descriptive, analytical type of research and with prospective of possible recommendations. It is evident, after the investigation, that the regulations in Colombia are complementary and seek transparency and legality, but there are gaps in contracting that leave room for irregular scenarios to arise.